Young Adult Sarawakian Purchase Intention On Junk Food Based On Packaging Design Elements - Fadilah, Siali; Kii, Winnie Lin Lin; Mahani Muhammad, Abdu Shakur; Norazirah, Ayob (Institute of Borneo Studies, UNIMAS, 2016)
An effective proactive product promotion is much needed to compete in the today’s competitive global market. Together, the product packaging has come to play an important role to influence consumers’ purchasing intention. The purpose of this study is to examine consumers’ perceptions towards packaging design elements and to determine the most influential factors on their purchase intention. A survey was conducted using self-administered structured questionnaires from 385 young adult respondents in Kota Samarahan and Kuching, Sarawak. Two junk food packaging with different package designs and attributes were used in this study. Major results show that the packaging colour, graphic, size, shape, material, and information have significant relationship with purchase intention. The finding could provide important insights to marketers and food manufacturers to adopt an appropriate packaging strategy for junk food to attract more sales from this particular group of consumers.